Bacteriological and Histological Verification of Diagnosis in Patients with Drug-Resistant Pulmonary Tuberculosis - Fatullaevich, Jumaev Mukhtor (Research Journal of Trauma and Disability Studies, 2024)
The development and implementation of promising technologies for the accelerated diagnosis of TB and the determination of the pathogen's LC is extremely important for providing highly effective treatment based on the selection of personalized chemotherapy regimens. One of the most promising and sought-after areas in the development of laboratory diagnosis of TB, which is supported by WHO, the Global Laboratory Initiative and the European Laboratory Initiative, is the use of molecular genetic methods (MGM) [10].